Mechanics of railway ballast behaviour - Lim, Wee Loon (2004)
It is important to have consistent ballast testing methods that provide results reflecting the performance of different ballast materials in the railway trackbed. In this research, extensive laboratory tests were conducted to investigate the correlation between simple ballast index tests, and box tests simulating ballast field loading conditions in a simplified and controlled manner. In the box test, a sleeper load of 40kN was applied to a simulated sleeper on the top of a sample of ballast in a box of dimensions 700x300x450mm. The ballast was tamped using a Kango hammer which caused particles to rearrange as the level of the sleeper was raised.